The Effects of Inference Instruction on the Reading Comprehension of English Learners With Reading Comprehension Difficulties. (September 2020) - Hall, Colby; Vaughn, Sharon; Barnes, Marcia A.; Stewart, Alicia A.; Austin, Christy R.; Roberts, Greg
Inference skill is one of the most important predictors of reading comprehension. Still, there is little rigorous research investigating the effects of inference instruction on reading comprehension. There is no research investigating the effects of inference instruction on reading comprehension for English learners with reading comprehension difficulties. The current study investigated the effects of small-group inference instruction on the inference generation and reading comprehension of sixth- and seventh-grade students who were below-average readers ( M = 86.7, SD = 8.1). Seventy-seven percent of student participants were designated limited English proficient. Participants were randomly assigned to 24, 40-min sessions of the inference instruction intervention ( n = 39) or to business-as-usual English language arts instruction ( n = 39). Membership in the treatment condition statistically significantly predicted higher outcome score on the Gates-MacGinitie Reading Test Reading Comprehension subtest ( d = 0.60, 95% confidence interval [CI] [0.16, 1.03]), but not on the other measures of inference skill.